2023
DOI: 10.1371/journal.pgen.1010590
|View full text |Cite
|
Sign up to set email alerts
|

Shuffling the yeast genome using CRISPR/Cas9-generated DSBs that target the transposable Ty1 elements

Abstract: Although homologous recombination between transposable elements can drive genomic evolution in yeast by facilitating chromosomal rearrangements, the details of the underlying mechanisms are not fully clarified. In the genome of the yeast Saccharomyces cerevisiae, the most common class of transposon is the retrotransposon Ty1. Here, we explored how Cas9-induced double-strand breaks (DSBs) directed to Ty1 elements produce genomic alterations in this yeast species. Following Cas9 induction, we observed a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
3
6
0
Order By: Relevance
“…For instance, a break outside a Ty element is more prone to generating rearrangements than a DSB induced within ( Hoang et al 2010 ). Also, the recent observation that a large proportion of recombination events induced by DSBs within LTR or Ty elements has breakpoints in unique sequences and generates frequent recombination between nontargeted repeats ( Fleiss et al 2019 ; Qi et al 2023 ) is consistent with the induction and repair of secondary DSBs, as shown for MIR ( Fig. 7 B–D).…”
Section: Discussionsupporting
confidence: 78%
“…For instance, a break outside a Ty element is more prone to generating rearrangements than a DSB induced within ( Hoang et al 2010 ). Also, the recent observation that a large proportion of recombination events induced by DSBs within LTR or Ty elements has breakpoints in unique sequences and generates frequent recombination between nontargeted repeats ( Fleiss et al 2019 ; Qi et al 2023 ) is consistent with the induction and repair of secondary DSBs, as shown for MIR ( Fig. 7 B–D).…”
Section: Discussionsupporting
confidence: 78%
“…For instance, a break outside a Ty element is more prone to generate rearrangements than a DSB induced within (Hoang et al 2010). Also, the recent observation that a large proportion of recombination events induced by DSBs within LTR or Ty elements have breakpoints in unique sequences and generate frequent recombination between non-targeted repeats (Qi et al 2023;Fleiss et al 2019) is consistent with the induction of secondary DSBs, as shown for MIR.…”
Section: Expanded Sequence Space For the Generation Of Repeat-mediate...mentioning
confidence: 71%
“…4A , the SNP microarray pattern showed that two chromosomal regions (bp 1 to 635650 of chromosome II and bp 1 to 182683 of chromosome XIII) were amplified, and two regions (bp 644285 to the right end of chromosome II and bp 183803 to the right end of chromosome XIII) were deleted in isolate LF4. According to our previous work ( 26 ), the majority of “paired” terminal deletions and duplications are the results of translocations between a centromere-containing fragment and an acentric fragment to form monocentric recombined chromosomes. In the LF4 lane of the pulsed-field gel electrophoresis (PFGE) results, a new band with a size of 818 kb was detected ( Fig.…”
Section: Resultsmentioning
confidence: 98%